2005
DOI: 10.1590/s0100-72032005000800002
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmose aguda: estudo da freqüência, taxa de transmissão vertical e relação entre os testes diagnósticos materno-fetais em gestantes em estado da Região Centro-Oeste do Brasil

Abstract: Objetivos: estabelecer a freqüência da toxoplasmose aguda em gestantes, a taxa de transmissão vertical e o resultado perinatal dos fetos infectados. Objetivou-se, ainda, avaliar a relação entre os principais testes materno-fetais de diagnóstico da toxoplasmose durante a gestação, bem como a relação entre faixa etária e a infecção aguda pelo Toxoplasma gondii. Métodos: estudo prospectivo longitudinal com 32.512 gestantes submetidas à triagem pré-natal pelo Programa de Proteção à Gestante de Mato Grosso do Sul, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
2
28

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 12 publications
(27 reference statements)
2
29
2
28
Order By: Relevance
“…Regarding maternal age for acute exposure to Toxoplasma gondii during pregnancy, a mean age of 22.1 years was found, similar to the mean age of 23 years reported by Figueró et al and 26.3 years reported by Varella et al 11,12 . Although in disagreement with other studies, maternal schooling greater than 9 years was not found to be a protective factor against the disease 13,14 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Regarding maternal age for acute exposure to Toxoplasma gondii during pregnancy, a mean age of 22.1 years was found, similar to the mean age of 23 years reported by Figueró et al and 26.3 years reported by Varella et al 11,12 . Although in disagreement with other studies, maternal schooling greater than 9 years was not found to be a protective factor against the disease 13,14 .…”
Section: Discussionsupporting
confidence: 87%
“…< 30%). This result may indicate a delay in starting prenatal care or in delivering results to assistant doctors, as the avidity test was only useful for the diagnosis during the first trimester of pregnancy (up to 16 weeks at the most) according to some authors 4,11,15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…This is a challenging public health situation with respect to planning and devising a triage strategy for this disease in a practical and comprehensive manner that would improve the treatment of affected pregnant women. These measures would contribute to a reduction in the morbidity/mortality of the mother and fetus, and thus improve health indicators [10][11][12] .…”
Section: Article/artigomentioning
confidence: 99%
“…These reports include studies on the prevalence of toxoplasmosis in pregnant women in the state (Figueiró-Filho et al 2005), whose result was only 0.42%, seroprevalence studies in animals such as horses by immunoϐluorescence (Larangeira et al 1985) with 32.8% of positive animals and pampas deer (Ozotocerus bezoarticus) in the region near the Nhecolândia, and found 12% seropositive animals through various serological techniques (Ferreira et al 1997). In the last decade, Silva (2005) evaluated 15 horses from seven rural property subregions of the Pantanal Mato Grosso do Sul (including the sub-region Nhecolândia) and showed only 1.33% of animals positive by hemagglutination test, however, no animals were positive in the sub-region Nhecolândia.…”
Section: Resultsmentioning
confidence: 99%